2019
DOI: 10.18632/aging.102562
|View full text |Cite
|
Sign up to set email alerts
|

Improved therapeutic effects on diabetic foot by human mesenchymal stem cells expressing MALAT1 as a sponge for microRNA-205-5p

Abstract: Diabetic foot (DF) is a common complication of high severity for diabetes, a prevalent metabolic disorder that affects billions of people worldwide. Mesenchymal stem cells (MSCs) have a demonstrative therapeutic effect on DF, through their generation of pro-angiogenesis factors, like vascular endothelial growth factor (VEGF). Recently, genetically modified MSCs have been used in therapy and we have shown that depletion of micoRNA-205-5p (miR-205-5p) in human MSCs promotes VEGF-mediated therapeutic effects on D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…83 Zhu et al overexpressed MALAT1 in MSCs. 84 When the modified MSCs were transplanted into wound tissues in STZ-induced diabetic mice, higher vessel density was detected, which reflected promotion of the angiogenesis phase. Further research showed that MALAT1 played its role by downregulating the expression of miR-205-5p.…”
Section: Proliferation Stagementioning
confidence: 99%
“…83 Zhu et al overexpressed MALAT1 in MSCs. 84 When the modified MSCs were transplanted into wound tissues in STZ-induced diabetic mice, higher vessel density was detected, which reflected promotion of the angiogenesis phase. Further research showed that MALAT1 played its role by downregulating the expression of miR-205-5p.…”
Section: Proliferation Stagementioning
confidence: 99%
“… 27 lncRNAs play an epigenetic regulatory role by regulating methylation and histone modification; 16 , 28 they also interact with RNA molecules or protein complexes for transcriptional regulation 8 , 28 , 29 and can act as a molecular sponge of miRNAs to regulate downstream target genes for post-transcriptional regulation. 30 , 31 , 32 In addition, lncRNAs can also affect protein expression and interfere with protein binding. 33 , 34 , 35 , 36 , 37 Recent studies have shown that lncRNAs are key regulators of cell proliferation, differentiation, apoptosis, and other cell biological processes, thereby regulating wound healing ( Figure 3 ).…”
Section: Ncrnamentioning
confidence: 99%
“…1 Diabetic foot ulcers (DFUs) are a serious complication of this metabolic disease that arises as a consequence of impaired wound healing, resulting in secondary infections and the potential need for limb amputation, thus negatively impacting patient quality of life. 2 Many efforts have been made to explore the mechanistic basis for DFU onset in order to improve patient healing activity. 3 In one study, the lncRNA H19/miR-152-3p/PTEN axis was shown to function as a critical regulator of wound repair in individuals with diabetes, indicating that it may be a viable therapeutic target in the context of DFU development.…”
Section: Introductionmentioning
confidence: 99%